The honorable Hudson Bay Company [electronic resource]. - Robinson, H. M. (Henry Martin), 1845-1907 ([New York? : s.n., 1879)
From: Harper's new monthly magazine. Caption title. Attributed to H.M. Robinson--Provincial Archives of British Columbia. Electronic reproduction. Mode of access: Internet. 44